Effect of a Clinical Nursing Practice Guideline for Preventing Infection among Neutropenia of Patients with Leukemia after Receiving Chemotherapy in Khon Kaen Hospital - Phongphayak, Sureeporn; Somjaivong, Busaba (Journal of health and health management, 2022)
This quasi-experimental research aimed to study the effect of a clinical nursing practice guideline for preventing infection among neutropenia of patients with leukemia after receiving chemotherapy in Khon Kaen Hospital. The purposive sampling were divided into a control group and an experimental group, with 25 patients in each group. The tools used to collect information consisted of a demographic data record, an infection screening form, and the clinical nursing practice guideline for preventing infection among neutropenia of patients with leukemia after receiving chemotherapy in Khon Kaen Hospital. The data were analyzed using descriptive statistics, and a comparison of infection and site of infection with the Chi-square test and Fisher’s exact test. The results found that 1) The experiment group and the control group had statistically different infections (p 0.001). 2) The control group had more than one site of infection than those in the experimental group with a statistical significance (p = 0.008). Based on the findings of this study, nurses should use the information in patient care in accordance with the guideline recommendations. Nurses must be able to assess infections, educate patients on self-care, and provide nursing care using specialized infection-reduction strategies. The pertinent environment must be managed as well, though.